2019
DOI: 10.1111/nyas.14117
|View full text |Cite
|
Sign up to set email alerts
|

Adults who stutter and metronome synchronization: evidence for a nonspeech timing deficit

Abstract: Speech timing deficits have been proposed as a causal factor in the disorder of stuttering. The question of whether individuals who stutter have deficits in nonspeech timing is one that has been revisited often, with conflicting results. Here, we uncover subtle differences in a manual metronome synchronization task that included tempo changes with adults who stutter and fluent speakers. We used sensitive circular statistics to examine both asynchrony and consistency in motor production. While both groups displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 57 publications
2
25
0
Order By: Relevance
“…We recently showed that individuals who stutter are more variable in responding to manipulations of pitch feedback while speaking, both in the number of compensatory responses and in the timing of those responses, and that this variability correlates with self-rated stuttering severity (Sares et al, 2018). The results of this and other behavioral studies (Kalinowski et al, 1993;Cai et al, 2014) point to a timing problem during auditory-motor behavior, something that also appears to extend to non-speech (Cooper and Allen, 1977;Ward, 1997;Boutsen et al, 2000;Subramanian and Yairi, 2006;Falk et al, 2015;van de Vorst and Gracco, 2017;Sares et al, 2019). Neuroimaging studies have identified differences in motor and auditory regions of the brain in adults who stutter (AWS; Foundas et al, 2001;Brown et al, 2005;Nil et al, 2008;Chang et al, 2009;Kell et al, 2009;Beal et al, 2010Beal et al, , 2011Kikuchi et al, 2011;Budde et al, 2014;Belyk et al, 2015).…”
Section: Introductionmentioning
confidence: 56%
“…We recently showed that individuals who stutter are more variable in responding to manipulations of pitch feedback while speaking, both in the number of compensatory responses and in the timing of those responses, and that this variability correlates with self-rated stuttering severity (Sares et al, 2018). The results of this and other behavioral studies (Kalinowski et al, 1993;Cai et al, 2014) point to a timing problem during auditory-motor behavior, something that also appears to extend to non-speech (Cooper and Allen, 1977;Ward, 1997;Boutsen et al, 2000;Subramanian and Yairi, 2006;Falk et al, 2015;van de Vorst and Gracco, 2017;Sares et al, 2019). Neuroimaging studies have identified differences in motor and auditory regions of the brain in adults who stutter (AWS; Foundas et al, 2001;Brown et al, 2005;Nil et al, 2008;Chang et al, 2009;Kell et al, 2009;Beal et al, 2010Beal et al, , 2011Kikuchi et al, 2011;Budde et al, 2014;Belyk et al, 2015).…”
Section: Introductionmentioning
confidence: 56%
“…Furthermore, some rhythmic conditions, such as singing or speaking along with a metronome, frequently improve the speech fluency of people who stutter (21)(22)(23)(24). Altogether, these observations suggest that stuttering is related to a temporal processing deficit (25)(26)(27)9,10,28).…”
Section: Introductionmentioning
confidence: 93%
“…-Phase Locking Value (PLV), characterizing the consistency of the beat-tap synchrony, defined as the norm of the sum of all the 𝑃𝐴 44444⃑ vectors (𝑃𝐴 44444⃑ is a unit vector of phase PA in a plane) divided by their number (Lachaux et al, 1999; Sares et al, 2019). In case the beattap asynchrony, and therefore the PA values, remain constant over a complete tapping train, the corresponding 𝑃𝐴 44444⃑ vectors align and their sum results in a vector of maximum length (i.e., ideally a PLV of 1).…”
Section: Extracted Descriptorsmentioning
confidence: 99%
See 2 more Smart Citations